Multiphysics simulation and experiment of a thrust bearing in scroll compressors. (February 2020) - Kim, Min-Su; Shim, Jaesool; Kim, Jeonghun; Jang, Dae-Gyeom; Park, Sang-Shin
Abstract: In this study, a quasi-dynamic lubrication model of a thrust bearing is developed to identify the behaviors of scroll compressors. The present model is comprehensive and accurate with fewer assumptions. It is composed of the Reynolds equation for a lubrication film, an energy equation for temperature distribution, and a stress–strain equation for deformation owing to fluid pressure, forces, moments, and thermal stress. For model validation, the film thickness of the thrust bearing was compared with the results of numerical simulation and experiment at two operating conditions. The numerical simulation is consistent with the experiment, showing an error within 5%. Highlights: A quasi-dynamic model of a thrust bearing in a scroll compressor is developed. Including refrigerant pressure, lubrication, and structural-thermal deformation. Calculated gas force, film thickness, attitude angle, pressure, and deformation. Accuracy is validated with experiment by measuring film thickness. Thermal deformation model provides the most precise result.